p$ -ADIC HODGE THEORY FOR RIGID-ANALYTIC VARIETIES - SCHOLZE, PETER (Forum of mathematics. Pi, 2013)
We give proofs of de Rham comparison isomorphisms for rigid-analytic varieties, with coefficients and in families. This relies on the theory of perfectoid spaces. Another new ingredient is the pro-étale site, which makes all constructions completely functorial.